2004
DOI: 10.1111/j.1523-1755.2004.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing renal graft function in clinical trials: Can tests predicting glomerular filtration rate substitute for a reference method?

Abstract: None of these formulas seems to be able to safely substitute for inulin clearance. In clinical trials, renal graft function should be preferably assessed using a reference method of GFR measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 22 publications
7
97
2
Order By: Relevance
“…This is partly explained by the fact that equations based on creatinine considerably overestimate GFR in renal transplantation (154)(155)(156). Overall, equations using CysC appear to offer better predictive performance, although it remains to be shown that this improvement in prediction is clinically significant (52, 131, 133, 157, 158).…”
Section: Utility Of Cysc In Transplantationmentioning
confidence: 89%
“…This is partly explained by the fact that equations based on creatinine considerably overestimate GFR in renal transplantation (154)(155)(156). Overall, equations using CysC appear to offer better predictive performance, although it remains to be shown that this improvement in prediction is clinically significant (52, 131, 133, 157, 158).…”
Section: Utility Of Cysc In Transplantationmentioning
confidence: 89%
“…This formula compares favorably with others in terms of dispersion when compared with inulin clearance in the renal transplant population (17). Proteinuria was measured from a 24-h urine collection.…”
Section: Determinationsmentioning
confidence: 99%
“…The Modification of Diet in Renal Disease method was used to estimate creatinine clearance because it has been shown that values that are derived by this formula correlate better than other available equations with true GFR in transplant recipients (10,11). Biopsy-confirmed acute rejection (BCAR) and chronic allograft nephropathy (CAN) were defined according to Banff 93 and 97 criteria, respectively (12,13).…”
Section: Variables and Definitions Of Variablesmentioning
confidence: 99%